Photochemical synthesis and device application of acene–phenacene hybrid molecules, dibenzo[n]phenacenes (n = 5–7). Issue 39 (23rd April 2021) - Zhang, Yanting; Eguchi, Ritsuko; Hamao, Shino; Goto, Kenta; Tani, Fumito; Yamaji, Minoru; Kubozono, Yoshihiro; Okamoto, Hideki
Abstract : Dibenzo[ n ]phenacenes (DB n P, n = 5–7) were applied to the active layers of p-channel FETs and their effective mobilities were evaluated to demonstrate that C 2h -symmetrical DB6P showed superior performance to the C 2v -symmetrical homologues. Abstract : Dibenzo[ n ]phenecenes (DB n Ps, n = 5–7) were conveniently synthesised through Mallory photocyclization as the key step. Effective mobilities of single-crystal field-effect transistors of DB n Ps were evaluated to demonstrate that C 2h -symmetrical DB6P shows higher performance than C 2v -symmetrical DB5P and DB7P .